New Holder - Type Inequalities for the Tracy-Singh and Khatri-Rao Products of Positive Matrices - Zeyad Abdel Al Ziz Al Zhour (Proceedings of ICMSA, 2005)
Recently, the authors establised a number of inequalities involving Khatri-Rao product of two positives matrices. Here, in this paper, the result are establised in three ways. First, we find new Holder-type inequalities for Tracy-Singh and Khatri-Rao products products of positive semi-devinite matrices. Second, the result are extended to provide estimates of sums of the Khatri-Rao and Tracy-Singh products of any finite number of positive semi-definite matrices. Three, the result lead to inequalities involving the Hadamard and Kronecker, as a special case.